Optimalisasi LAN Untuk Kualitas Service File Transfer Di PT. Telkom Gambir - Tengangatu, Paul Filson (Universitas Multi Data Palembang, 2025)
The use of File Transfer at Telkom Gambir is important, because this Telkom Company Branch consists of divisions that play an important role in the installation and maintenance of GPON networks in Central Jakarta. Therefore, the author seeks a way to improve the quality of File Transfer services on the performance of the LAN network and the Telkom Gambir network topology by creating a simulation using Riverbed Modeler. Then the author compares the simulation using traffic shaping techniques and bandwidth management techniques that are known to the author, to improve the quality of File Transfer services on the Telkom Gambir network. By analyzing the results of the Global Statistics simulation from the File Transfer scenario and comparing the scenario with the current running system. Based on the author's analysis, setting limits on the Access Point is the best scenario to improve the quality of service of File Transfer. This is because setting limits on the Access Point in addition to having better quality of service performance than the current system also provides the best Traffic Received and Traffic Sent from all scenarios.